Structural Requirements and Plasticity of Receptor-Binding Domain in Human Coronavirus Spike - Li, Yajuan; Zheng, Peiyi; Liu, Tingting; Shi, Cuixiao; Wang, Bo; Xu, Yuanhong; Jin, Tengchuan (Frontiers in Molecular Biosciences, 2022)
The most recent human coronaviruses, including the severe acute respiratory syndrome coronavirus-2, causing severe respiratory tract infection and high pathogenicity, bring significant global public health concerns. Coronavirus infections are initiated by recognizing host cell receptors by S1 subunit of spike protein, then S2 fusing to cell membrane by S2. However, the human coronavirus spike undergoes frequent mutation, which may result in diverse pathogenesis and infectivity. In this review, we summarise some of these recent structural and mutational characteristics of receptor-binding domain (RBD) of human coronavirus spike protein and their interaction with specific human cell receptors and analyze the structural requirements and plasticity of RBD. Stability of spike protein, affinity toward receptor, virus fitness, and infectivity are factors controlling the viral tropisms. Thus understanding the molecular details of RBDs and their mutations is critical in deciphering virus evolution. Structural information of spikes and receptors of human coronaviruses reveals the molecular mechanism of host-microbe interaction and pathogenesis and helps develop effective drugs to control these infectious pathogens and cope with the future emerging coronavirus outbreaks.